2013
DOI: 10.5491/shaw.2013.4.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological Evaluations of Rare Earths and Their Health Impacts to Workers: A Literature Review

Abstract: In concert with the development of new materials in the last decade, the need for toxicological studies of these materials has been increasing. These new materials include a group of rare earths (RE). The use of RE nanotechnology is being considered in some green applications, to increase their efficiency by using nano-sized RE compounds, and therefore hazard evaluation and risk assessment are highly recommended. This review was conducted through an extensive contemplation of the literatures in toxicology with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
184
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 395 publications
(190 citation statements)
references
References 54 publications
1
184
0
5
Order By: Relevance
“…For instance, REEs can accumulate in human brains via blood circulation, which may induce neurotoxic effects (Hollriegl et al, 2010 andRim et al, 2013), cause lung diseases when inhaling dust and metal fumes (USEPA, 2012), and afflict patients with diseases such as leukemia, cancer, and birth defects of children (Ismail et al, 2001;Liang et al, 2014;Rim et al, 2013). In addition, high exposure levels of REEs may lead to liver function decline (Wei et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, REEs can accumulate in human brains via blood circulation, which may induce neurotoxic effects (Hollriegl et al, 2010 andRim et al, 2013), cause lung diseases when inhaling dust and metal fumes (USEPA, 2012), and afflict patients with diseases such as leukemia, cancer, and birth defects of children (Ismail et al, 2001;Liang et al, 2014;Rim et al, 2013). In addition, high exposure levels of REEs may lead to liver function decline (Wei et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The main spots for accumulation are the bones, liver, and lungs [156,159,160]. Some damage can be mentioned, such as cardiac, hepatic, hematological, and renal problems, besides effects in the gastrointestinal tract, in bones, in the central nervous system, and in the pulmonary and cytogenetic systems [79,156,[159][160][161][162]. Despite this, the current information is not enough to determine the safe levels of exposure in humans [160], with values found being described as temporary [163].…”
Section: Ecological and Human Health Risks Associated With Reementioning
confidence: 99%
“…Several studies involving effects of REE in experimental animals have reported an accumulation of these elements with time. The main spots for accumulation are the bones, liver, and lungs [156,159,160]. Some damage can be mentioned, such as cardiac, hepatic, hematological, and renal problems, besides effects in the gastrointestinal tract, in bones, in the central nervous system, and in the pulmonary and cytogenetic systems [79,156,[159][160][161][162].…”
Section: Ecological and Human Health Risks Associated With Reementioning
confidence: 99%
“…38 While the use of these lanthanides may lead to significant polarization gains, the free ion form of these lanthanides may lead to greater toxicity of the DNP sample, which must be considered prior to in vivo biomedical application. 39 One method used to combat the toxicity of rare earth metals is to encage these lanthanide ions with a chelating agent, thus rendering them relatively inert in the body. 40 Among the more prominent ligands used in gadolinium contrast agents are DTPA, 40,41 HP-DO3A, 42,43 and DOTA.…”
Section: Introductionmentioning
confidence: 99%